Measurement of single- and double-escape HPGe efficiency ratios for 60Co. (27th May 2020) - Burns, G J; Croft, S; Findlay, D J S; Škoro, G P
Abstract: As a by-product of another measurement, ratios of the single-escape (SE) and double-escape (DE) efficiencies relative to the full-energy-peak efficiency (FE) have been measured for two HPGe detectors for 60 Co. For a 2.5-cm-thick 95 cm 3 crystal the results were SE/FE = 0.000 48 ± 0.000 20 and 0.003 25 ± 0.000 24 for 1173 and 1332 keV gamma-rays, respectively, and DE/FE = 0.000 90 ± 0.000 17 and 0.003 41 ± 0.000 11 for 1173 and 1332 keV, respectively. For a 3.0-cm-thick 84 cm 3 crystal the results were SE/FE = 0.000 67 ± 0.000 32 and 0.003 79 ± 0.000 27 for 1173 and 1332 keV respectively, and DE/FE = 0.001 05 ± 0.000 28 and 0.004 29 ± 0.000 16 for 1173 and 1332 keV, respectively. These measurements may be of relevance in connection with Monte Carlo calculations of HPGe detector efficiencies, and may also suggest a path towards improved atomic cross-section measurements.